2019
DOI: 10.5194/acp-19-14721-2019
|View full text |Cite
|
Sign up to set email alerts
|

An increase in methane emissions from tropical Africa between 2010 and 2016 inferred from satellite data

Abstract: Abstract. Emissions of methane (CH4) from tropical ecosystems, and how they respond to changes in climate, represent one of the biggest uncertainties associated with the global CH4 budget. Historically, this has been due to the dearth of pan-tropical in situ measurements, which is particularly acute in Africa. By virtue of their superior spatial coverage, satellite observations of atmospheric CH4 columns can help to narrow down some of the uncertainties in the tropical CH4 emission budget. We use proxy column … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 87 publications
(125 reference statements)
14
110
0
Order By: Relevance
“…The downregulation of North American emissions is consistent with recent WetCHARTs updates (v1.2.1) represent substantially reduced methane emissions across regions categorized as partial wetland complexes (Lehner & Döll, 2004;Bloom et al, 2017). Recent studies found that WetCHARTs overestimates wetland emissions in the Congo Basin but underestimates in the Sudd region (Lunt et al, 2019;Parker et al, 2020b;Pandey et al, 2020). Our inversion is unable to resolve this spatial correction pattern, because of coarse resolution in the wetland state vector (both regions are in Sub-Sahara Africa, i.e., wetland region 10 in Figure 1).…”
Section: Wetland Emissionssupporting
confidence: 80%
See 1 more Smart Citation
“…The downregulation of North American emissions is consistent with recent WetCHARTs updates (v1.2.1) represent substantially reduced methane emissions across regions categorized as partial wetland complexes (Lehner & Döll, 2004;Bloom et al, 2017). Recent studies found that WetCHARTs overestimates wetland emissions in the Congo Basin but underestimates in the Sudd region (Lunt et al, 2019;Parker et al, 2020b;Pandey et al, 2020). Our inversion is unable to resolve this spatial correction pattern, because of coarse resolution in the wetland state vector (both regions are in Sub-Sahara Africa, i.e., wetland region 10 in Figure 1).…”
Section: Wetland Emissionssupporting
confidence: 80%
“…A number of inverse analyses previously used GOSAT observations to constrain methane emission estimates (Fraser et al, 2013;Monteil et al, 2013;Cressot et al, 2014;Alexe et al, 2015;Turner et al, 2015;Pandey et al, 2016;Pandey et al, 2017a;Miller et al, 2019;F. Wang et al, 2019a;Lunt et al, 2019;Maasakkers et al, 2019;Janardanan et al, 2020;Tunnicliffe et al, 2020;Yin et al, 2020). Maasakkers et al (2019) used 2010-2015 GOSAT observations to optimize gridded methane emissions, global OH concentrations, and their 2010-2015 trends.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse model suggested an overall underestimation in the prior for equatorial African countries (Figure 4f), such as Uganda, Tanzania, Sudan, and Kenya, though the annual emissions were lower for these countries. A recent study ( [60]) using GOSAT XCH 4 observations in their inversion reported overall larger emissions compared to prior over Africa with strong exceptions in the Congo basin. However, in our analysis, we found a slight increase in our posterior emissions over the Democratic Republic of Congo.…”
Section: Emission From Natural Sourcesmentioning
confidence: 89%
“…Tropical Africa is also a natural methane emitter (12% of global wetland emission, [59]) where the sources are wetlands, flood plain, riverine ecosystems, etc. Due to the seasonal migration of the intertropical convergence zone (ITCZ), the inundation extent is highly variable in these water bodies, and thus there is significant variability in the estimates of methane emission in this region ( [60]) and difficulty in models to capture the wetland emissions. Significant reductions were observed over boreal North America and Russia (Figure 3).…”
Section: Posterior Fluxes and Flux Correctionsmentioning
confidence: 99%
“…Inverse analyses of atmospheric methane observations using chemical transport models (CTM) provide a formal method for inferring methane emissions and their trends (Brasseur and Jacob, 2017). Global satellite observations of atmospheric methane columns from the shortwave infrared SCIAMACHY and GOSAT instruments have been widely used for this purpose (Bergamaschi et al, 2013;Wecht et al, 2014;Turner et al, 2015;Maasakkers et al, 2019;Miller et al, 2019;Lunt et al, 2019). Other inverse analyses have relied on in situ methane observations that have much higher precision, are more sensitive to surface emissions, and include isotopic information, but are much sparser (Pison et al, 2009;Bousquet et al, 2011;Miller et al, 2013;Patra et al, 2016;McNorton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%